1999
DOI: 10.1002/(sici)1097-0290(19990320)62:6<632::aid-bit2>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in batch cultures of Chinese Hamster Ovary cells

Abstract: One of the main problems in the culture of Chinese Hamster Ovary (CHO) cells continues to be the inability to maintain the viability of the cultures over an extended period of time. The rapid decline in viability at the end of the culture is exacerbated by the absence of serum. In trying to reduce the extent of death in these cultures, we first tried to determine the mode of death. We found that more than 80% of the cells in a standard serum-free batch culture of CHO cells in suspension died via apoptosis-as e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
73
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(80 citation statements)
references
References 51 publications
6
73
0
1
Order By: Relevance
“…Attaining the grams per liter production levels of biotherapeutics in today's commercial production processes relies upon the optimization of both mammalian cell culture and engineering methods. Inherent in current high density, protein-free mammalian cell cultures is the problem of cell death of which apoptosis can account for up to 80% in a typical fed-batch bioreactor, induced in response to insults such as nutrient and growth factor deprivation, oxygen depletion, toxin accumulation, and shear stress (Goswami et al, 1999). Apoptosis limits the maximum viable cell density, accelerates the onset of the death phase and potentially decreases heterologous protein yield (Chiang and Sisk, 2005;Figueroa et al, 2001Figueroa et al, , 2003Figueroa et al, , 2004Mastrangelo and Betenbaugh, 1998;Mercille and Massie, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attaining the grams per liter production levels of biotherapeutics in today's commercial production processes relies upon the optimization of both mammalian cell culture and engineering methods. Inherent in current high density, protein-free mammalian cell cultures is the problem of cell death of which apoptosis can account for up to 80% in a typical fed-batch bioreactor, induced in response to insults such as nutrient and growth factor deprivation, oxygen depletion, toxin accumulation, and shear stress (Goswami et al, 1999). Apoptosis limits the maximum viable cell density, accelerates the onset of the death phase and potentially decreases heterologous protein yield (Chiang and Sisk, 2005;Figueroa et al, 2001Figueroa et al, , 2003Figueroa et al, , 2004Mastrangelo and Betenbaugh, 1998;Mercille and Massie, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have turned to chemical and genetic strategies to inhibit the apoptotic signaling cascade from within the cell (Sauerwald et al, 2002. Researchers have found that over-expression of genes found upregulated in cancer cells can prolong viability in cells grown in bioreactors by preventing apoptosis upstream of caspase activation (Goswami et al, 1999;Mastrangelo et al, 2000;Meents et al, 2002;Tey et al, 2000a,b). Upregulation of these proteins in production cell lines effectively suppressed apoptotic signaling within the cell, thereby limiting cell death in order to maintain viability and increase biotherapeutic production in some cases.…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis is triggered by a cascade of cysteine proteases called caspases, which are activated in response to various insults that may develop in bioreactors during batch or fed batch cultures. It has been observed that apoptosis is a common mode of cell death in CHO culture, especially in the post-exponential growth phase (Franek and Dolnikova, 1991;Golstein et al, 1991;Goswami et al, 1999).…”
Section: Motivationmentioning
confidence: 99%
“…As nutrients are depleted and metabolic activity slows down, growth stops and apoptosis is triggered. Apoptosis accounts for the majority of cell death in bioreactors (Franek and Dolnikova, 1991;Golstein et al, 1991;Goswami et al, 1999) and so it significantly impacts cell density and viability, and thus product titer. A major cause for apoptosis in batch culture is likely depletion of vital nutrients such as glucose (Goswami et al, 1999) and amino acids such as glutamine and asparagine (Sanfeliu and Stephanopoulos, 1999;Simpson et al, 1998b).…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation